2019
DOI: 10.24018/ejers.2019.4.1.980
|View full text |Cite
|
Sign up to set email alerts
|

The Morphological Changes of SnS Thin Films Deposited on Stainless-Steel Substrates at Low Temperatures

Abstract: Orthorhombic tin sulfide (SnS) thin films have been deposited on stainless steel (SS) substrates by Chemical Bath Deposition (CBD) at 25, 35 and 70 °C with a deposit time of 8 hours each one. XRD analysis showed that samples obtained at 25 °C and 70 °C present very small diffraction peaks. This can be attributed in the case of the sample obtained at 25 degrees, that the crystallization process is not completed because the temperature is so low and in case of the sample deposited at 75 degrees, a redissolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This work uses a method first reported in 2021 [24] that allows us to grow orthorhombic SnS thin films of 390 nm in 3.5 h. There are reported methods to obtain orthorhombic SnS by CBD with deposition times of 8, 17, 24, 30, and up to 40 h [20,21,[25][26][27] and just a few with times below 6 h [28][29][30]. We study the effect of deposition time and percentage of Sn precursor on structural and optical properties of SnS thin films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work uses a method first reported in 2021 [24] that allows us to grow orthorhombic SnS thin films of 390 nm in 3.5 h. There are reported methods to obtain orthorhombic SnS by CBD with deposition times of 8, 17, 24, 30, and up to 40 h [20,21,[25][26][27] and just a few with times below 6 h [28][29][30]. We study the effect of deposition time and percentage of Sn precursor on structural and optical properties of SnS thin films.…”
Section: Introductionmentioning
confidence: 99%
“…This work is based on a method first reported in 2021 [24], which focuses on studying the PH effect on the chemical deposited SnS films, using a deposition time of 3 h. It is important to note that the reported methods to obtain orthorhombic SnS by CBD use deposition times of 8, 17, 24, 30, and up to 40 h [20,21,[25][26][27] and just a few use times below 6 h [28][29][30]. In the work of Higareda et al [24], they observed a sulfur excess in the chemical solution when the amount of tin precursor was varied in percentages lower than 5%.…”
Section: Introductionmentioning
confidence: 99%